2017
DOI: 10.1177/1476127017696282
|View full text |Cite
|
Sign up to set email alerts
|

Effects of functional focus on bounded momentum: Examining firm- and industry-level alliances

Abstract: Building on strategic momentum and alliance studies, we theoretically explain and test the non-monotonicity of the alliance momentum of same- or cross-functional-type alliances. We theorize about critical drivers that generate bounded momentum and further argue whether function-specific momentum occurs sequentially or simultaneously. We examine cross-border alliances of 32 international airlines from 1945 to 1994 and find that the inverted U-shaped pattern of alliance momentum holds for same-type but not for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
1
1
0
Order By: Relevance
“…First, whereas other studies have suggested curvilinear performance effects as a result of volume or diversity of actions (Jiang et al, 2010;Wuyts and Dutta, 2014), the present findings are consistent with the ABV to suggest both an interactive and curvilinear effect when simultaneously assessing volume and diversity. The findings also align with and extend recent research challenging the typical linear assumptions in prior research (Connelly et al Park et al, 2018) to suggest that, when assessed in a concurrent model, competitive and cooperative actions yield diminishing returns, and these effects are moderated by action diversity for competitive actions. While previous research examining independent competitive and cooperative action repertoires has applied the ABV framework to understand attentional constraints in relation to actions of the firm (Filiou and Massini, 2018;Kilduff, 2019), the present study extends these findings to assess a more holistic model of firm actions by empirically assessing both action types in an integrative model.…”
Section: Research Implicationssupporting
confidence: 87%
“…First, whereas other studies have suggested curvilinear performance effects as a result of volume or diversity of actions (Jiang et al, 2010;Wuyts and Dutta, 2014), the present findings are consistent with the ABV to suggest both an interactive and curvilinear effect when simultaneously assessing volume and diversity. The findings also align with and extend recent research challenging the typical linear assumptions in prior research (Connelly et al Park et al, 2018) to suggest that, when assessed in a concurrent model, competitive and cooperative actions yield diminishing returns, and these effects are moderated by action diversity for competitive actions. While previous research examining independent competitive and cooperative action repertoires has applied the ABV framework to understand attentional constraints in relation to actions of the firm (Filiou and Massini, 2018;Kilduff, 2019), the present study extends these findings to assess a more holistic model of firm actions by empirically assessing both action types in an integrative model.…”
Section: Research Implicationssupporting
confidence: 87%
“…For instance, momentum theory suggests that search and change continue, once initiated, even if the performance shortfall is resolved. Momentum theory has received empirical support in the domains of acquisitions (e.g., Amburgey & Miner, 1992;Baum, Li, & Usher, 2000), alliances (Park, Martin, Lee, & Mezias, 2017), and organizational change (see Beck, Brüderl, & Woywode, 2008 for a review). This need not imply that satisficing does not function in problemistic search.…”
Section: Performance Improvementmentioning
confidence: 99%